Efficient Charge Extraction in Thick Bulk Heterojunction Solar Cells through Infiltrated Diffusion Doping. Issue 8 (27th January 2014) - Kim, Junghwan; Yu, Kilho; Kim, Heejoo; Kwon, Sooncheol; Kim, Geunjin; Kwon, Kyungchoon; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> A new strategy for improving the charge extraction in thick bulk heterojunction (BHJ) polymer solar cells (PSCs) is reported. By the deposition of a solution‐processed vanadium oxide (s‐VOx) onto BHJ active layers, conductive charge‐transport channels are formed inside the active layer via a charge‐transfer doping reaction between the lone‐pair electrons of the sulfur atoms in the polymer and the Lewis‐acidic vanadium atoms of the s‐VOx. Because the charge‐transport channels significantly reduce charge recombination in the BHJ films, high internal quantum efficiencies (IQEs) of over 80% are achieved in the thick inverted PSCs (≈420 nm). This finding represents a new strategy for improving the efficiency and feasibility of printable photovoltaic devices.